Hegemony, Counter-Hegemony and Food Systems Literacy: Transforming the Global Industrial Food System. (14th May 2019) - Rose, Nicholas; Lourival, Izo
Abstract: National and global food systems are beset by intersecting and mutually reinforcing crises of public and ecological health. The locus of these crises resides primarily in the excessive concentration of corporate power and control. Deploying a Gramscian theory of politics as a contribution to the ongoing development of a critical food-based environmental education pedagogy, this article argues that transformative change requires the mass exercise of food citizenship directed towards the realisation of a socially just and ecologically sustainable food system, as contemplated by the principles of food sovereignty. The article argues further that food citizenship in turn presupposes levels of engagement and motivation that will only come from processes of transformative learning and critical consciousness-raising through an emerging form of environmental education: critical food systems literacy.